Economic Growth and Sectoral Change under Resource Reallocation Costs - Thomas M. Steger (ETH Zurich, CER-ETH - Center of Economic Research, 2003)
A general growth model with explicit resource reallocation costs is set up. A new feature is the property of hysteresis (i.e. a continuum of stationary equilibria) in closed-economy growth models. Employing a linear model the hysteresis range and the consequences for the long-run growth rate are determined analytically. The most important conclusions are the following: (1) An economy's long-run position may depend critically on the initial intersectoral allocation pattern as well as on the efficiency of the resource reallocation sector; (2) if we interpret the resource reallocation sector as a specific part of the education sector, there is a straightforward possibility for the government to reduce the range of hysteresis and hence the dependence on initial conditions; (3) international trade is an important device to overcome the negative consequences of high resource reallocation costs for long-run growth.
Keywords: O0; N1; 330; Sectoral change; economic growth; resource reallocation costs; hysteresis; multiplicity of equilibria; Subsistenzwirtschaft; Wachstumstheorie; Wirtschaftliche Konvergenz; Theorie; Entwicklungsländer